ANALISA TINGKAT KEPUASAN ALUMNI TERHADAP KUALITAS PELAYANAN FAKULTAS EKONOMI UNIVERSITAS PEKALONGAN - Muhammad Shofiyuddin; Amalia Ilmiani (LPPM Universitas Pekalongan, 2013)
This study aims to analyze customer satisfaction (collegiate) for services provided in college. The method of study is by using questionnaire with sample of population taken from students of Economic Faculty of Pekalongan University who graduated in September 2012. This research is a descriptive study, the type of design conclusive that aims to describe the character or function of the research on a group. The results of this research find that satisfaction of service perceived by the students of the Faculty of Economics, University of Pekalongan is in conformity with what is expected however to laboratory facilities is very important to note and it is important to be completed. Keyword: Students’ Satisfaction, service quality.